Transpoiesis: the art of doing organization without becoming one - Schröder, Christian (Frontiers in Education, 2025)
This paper uses the concept of transpoiesis to describe the mechanisms that sustain social movements. Emerging from ethnographic research on the World Social Forum (WSF) and inspired by systems theory, transpoiesis emphasizes the dynamic balance within social movements between decentralized organization and strategic coherence. This differentiates it from autopoiesis, which focuses on self-sustaining systems that maintain and reproduce their structure autonomously through internal processes, rather than emphasizing the dynamic balance between decentralized organization and strategic coherence. Transpoiesis offers a particularly instructive model in the digital age, when classical explanations often fail to account for the rapid pace of change, innovation, flexibility and decentralized collaboration that characterize modern organizations. The concept aids in understanding how social movements build collective identities, navigate organizational dynamics, structure collective learning, and contribute to social change. Moreover, it reflects the broader shift toward network-based arrangements in contemporary organizations, an adaptation to the complexities of the digital environment.